Fusobacterium nucleatum Activates Endoplasmic Reticulum Stress to Promote Crohn’s Disease Development via the Upregulation of CARD3 Expression - Cao, Pan; Chen, Yongyu; Guo, Xufeng; Chen, Yan; Su, Wenhao; Zhan, Na; Dong, Weiguo (Frontiers in Pharmacology, 2020)
There is increasing evidence that members of the gut microbiota, especially Fusobacterium nucleatum (F. nucleatum), are associated with Crohn's disease (CD), but the specific mechanism by which F. nucleatum promotes CD development is unclear. Here, we first examined the abundance of F. nucleatum and its effects on CD disease activity, and explored whether F. nucleatum aggravated intestinal inflammation and promoted intestinal mucosal barrier damage in vitro and in vivo. Our data showed that F. nucleatum was enriched in 41.21% of CD tissues from patients and was correlated with the clinical course, clinical activity, and refractory behavior of CD (P < 0.05). In addition, we found that F. nucleatum infection is involved in activating the endoplasmic reticulum stress(ERS) pathway during CD development to promote intestinal mucosal barrier destruction. Mechanistically, F. nucleatum targeted CARD3 to activate the ERS pathway and promote F. nucleatum-mediated mucosal barrier damage in vivo and in vitro. Thus, F. nucleatum coordinates a molecular network involving CARD3 and ERS to control the CD process. Measuring and targeting F. nucleatum and its associated pathways will provide valuable insight into the prevention and treatment of CD.